RAMP1 Is a Direct NKX3.1 Target Gene Up-Regulated in Prostate Cancer that Promotes Tumorigenesis - Logan, Monica (American Society for Investigative Pathology, 2013)
The homeodomain-containing transcription factor, NKX3.1, plays an important role in the suppression of prostate tumorigenesis. Herein, we identify the receptor activity–modifying protein 1 (RAMP1) as a direct NKX3.1 target gene through analysis of chromatin immunoprecipitation coupled to massively parallel sequencing and gene expression data. RAMP1 is a coreceptor for certain G-protein–coupled receptors, such as the calcitonin gene-related peptide receptor, to the plasma membrane. We found that RAMP1 expression is specifically elevated in human prostate cancer relative to other tumor types. Furthermore, RAMP1 mRNA and protein levels are significantly higher in human prostate cancer compared with benign glands. We identified multiple NKX3.1 binding sites in the RAMP1 locus in human prostate cancer cells and in the normal mouse prostate. Analyses of Nkx3.1 knockout mice and human prostate cancer cell lines indicate that NKX3.1 represses RAMP1 expression. Knockdown of RAMP1 by shRNA decreased prostate cancer cell proliferation and tumorigenicity in vitro and in vivo. By using gene expression profiling and pathway analyses, we identified several cancer-related pathways that are significantly altered in RAMP1 knockdown cells, including the mitogen-activated protein kinase signaling pathway. Further experiments confirmed a reduction in MAP2KI (MEK1) expression and phosphorylated-extracellular signal–regulated kinase 1/2 levels in RAMP1 knockdown cells. These data provide novel insights into the role of RAMP1 in promoting prostate tumorigenesis and support the potential of RAMP1 as a novel biomarker and possible therapeutic target in prostate cancer.